2011
DOI: 10.1155/2011/893208
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heparan Sulfate 2-O-Sulfotransferase in Prostate Cancer Cell Proliferation, Invasion, and Growth Factor Signaling

Abstract: Heparan-sulfate proteoglycans (HSPGs) are required for maximal growth factor signaling in prostate cancer progression. The degree of sulfate modification on the covalently attached heparan sulfate (HS) chains is one of the determining factors of growth factor-HSPG interactions. Sulfate groups are transferred to HS chains via a series of O-sulfotransferases. In the present study, we demonstrate that Heparan sulfate 2-O-sulfotransferase (2OST) is essential for maximal proliferation and invasion of prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…When CaP cells were treated with pso, invasion by CaP cells was significantly inhibited (Figure 5B). We observed PC-3 cells potently invaded through matrigel when compared to C4-2B cells and the results are consistent with published data [30][31][32][33]. Furthermore, we confirmed that pso treatment decreased the expression of slug, vimentin, and bcatenin in PC-3 cells by Western blot analysis (Figure 5C).…”
Section: Pso-induced Ros Inhibits Migration and Invasion Of Cap Cellssupporting
confidence: 92%
“…When CaP cells were treated with pso, invasion by CaP cells was significantly inhibited (Figure 5B). We observed PC-3 cells potently invaded through matrigel when compared to C4-2B cells and the results are consistent with published data [30][31][32][33]. Furthermore, we confirmed that pso treatment decreased the expression of slug, vimentin, and bcatenin in PC-3 cells by Western blot analysis (Figure 5C).…”
Section: Pso-induced Ros Inhibits Migration and Invasion Of Cap Cellssupporting
confidence: 92%
“…Expression of HS3ST2 is epigenetically silenced in lung cancers, where it functions to suppress tumor growth and invasion [80]. By contrast, HS2ST1, HS3ST3B1, HS3ST4, and HS6ST1 and 2 promote cell proliferation, invasiveness and tumor angiogenesis [77, 81-83], presumably via increased HS sulfation and enhanced growth factor signaling.…”
Section: Box 1: Synthesis and Modification Of Hspgsmentioning
confidence: 99%
“…The O-sulphotransferases (HSSTs) group comprises the largest cluster of genes encoding the HS biosynthetic machinery and whose expression is most often deregulated in various tumors, many interesting examples of which have been described. Concerning HS2ST1, studies have demonstrated that it is crucial for cell proliferation and invasion, and its expression correlates with increasing metastatic capacity, especially in prostate cancer [13]. Additionally, overexpression of HS6ST1 in ovarian cancer and HCC, and overexpression of HS6ST2 in colorectal cancer and ovarian cancer has been described [14].…”
Section: Genetic Alterations and Transcriptional Controlmentioning
confidence: 99%